Sisters, Schoolgirls, and Sleuths : Girls' Series Books in America - Carpan, Carolyn (Lanham, Md. : Scarecrow Press, 2009)
"In Sisters, Schoolgirls, and Sleuths: Girls' Series Books in America, Carolyn Carpan provides a social history of girls' series fiction published in America from the mid-nineteenth century through the early twenty-first century."--Back cover.
Victorian and Vassar girls: nineteenth-century origins of girls' series fiction -- Schoolgirls and sorority sisters: progressive era high school and college series -- Adventure girls and the new woman: from the progressive era to the jazz generation -- The secret of Nancy Drew and her sister sleuths: -- Career girls and World War II -- Romances and revisions: the junior novel and the new Nancy Drew -- Romance meets reality: girls' series fiction and the second wave of feminism -- Sweet dreams for teen queens: romance renaissance in the Reagan era -- High school horrors! Genre fiction for teens.
Includes bibliographical references and index.
Keywords: Children's stories, American -- History and criticism; Young adult fiction, American -- History and criticism; Girls in literature; Teenage girls in literature; Children's literature in series -- History and criticism; Girls -- Books and reading -- United States -- History; Children's literature in series; Children's stories, American; Girls; Girls -- Books and reading; Literature; Teenage girls; Young adult fiction, American; United States; Criticism, interpretation, etc; History